Simultaneous Analysis of Dopamine and Ascorbic Acid Using Polymelamine/Gold Nanoparticle-Modified Carbon Paste Electrode - Muji Harsini; Ainy Nur Farida; Erna Fitriany; Denok Risky Ayu Paramita; Afaf Baktir; Fredy Kurniawan; Satya Candra Wibawa Sakti; Yudhi Dwi Kurniawan; Bernadeta Ayu Widyaningrum (Indonesian Journal of Chemistry, 2024)
Modification of electrode using polymelamine (PM) and gold nanoparticles (AuNPs) has been successfully developed via electropolymerization and electrodeposition onto carbon paste electrode (CPE) using cyclic voltammetry (CV) technique. The modified electrode (AuNPs/PM/CPE) was applied as voltammetry sensors in a simultaneous of dopamine (DA) and ascorbic acid (AA). AuNPs/PM/CPE presented an effective surface area 5 times wider than CPE and demonstrated good electrocatalytic performance in the oxidation of DA and AA in 0.1 M phosphate buffer solution (pH 3) with a scan rate of 100 mV s−1. The differential pulse voltammetry (DPV) technique was chosen as the best method for separating potential peaks of DA and AA. The linear response for determining DA and AA using the DPV technique produced a concentration range of 0.1–13 and 0.4–12 µM with coefficient linearity of 0.9999 and 0.9997, the limit of detection of 0.1405 and 0.2187 µM, the accuracy of 89.62–109.16%, and 83.63–105.08%, and the precision of 0.017–0.701% and 0.066–0.626%, respectively. In addition, this electrode was applied in a real sample of infant urine with a concentration of 1 µM by spike method and found 98.86 and 98.28% as percent recovery of DA and AA, respectively.